Heavy metal exposure and its impact on inflammatory ratios in minors: The mediating role of BMI - Xinpeng Li; Lu Han (PLoS ONE, 2025)
Background Despite existing evidence that endocrine-disrupting chemicals like heavy metals exposure impairs health of minors, the association between the exposures and inflammatory ratios remains uncertain. This study aims to investigate the relationship between heavy metal exposure and inflammatory ratios, focusing on BMI as a potential mediator in this association. Method We conducted a retrospective cross-sectional analysis from the NHANES 2007–2018. 14,007 minors were categorized into different age groups, and analyses were performed based on demographic characteristics. Multiple linear regression and mediation analysis were applied to asses associations between heavy metal concentrations and inflammatory ratios, with BMI included as a mediating variable. Results The participants were divided into four age groups: toddlers (2487), preschool children (2297), school-age children (5019), and teenagers (4204). Blood Pb was positively correlated with LMR (β = 0.70, 95% CI: 0.60–0.81) and PNR (β = 14.88, 95% CI: 12.29–17.47), with 25.89% and 27.02% of these associations mediated by BMI. Negative correlations were observed between Pb and inflammation ratios, including NLR (β = −0.29, 95% CI: −0.34 – −0.24), PLR (β = −10.35, 95% CI: −12.61– −8.08), and NMR (β = −0.63, 95% CI: −0.78 – −0.48), with BMI accounting for 37.64%, 22.40%, and 39.59% of these effects, respectively. Blood Cd and Hg were also correlated with these ratios, with BMI consistently mediating these associations. Conclusions BMI serves as a significant mediator between blood heavy metals and inflammatory ratios among minors.